2010
DOI: 10.1111/j.1654-1103.2010.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Species and structural diversity of church forests in a fragmented Ethiopian Highland landscape

Abstract: Question: Thousands of small isolated forest fragments remain around churches (''church forests'') in the almost completely deforested Ethiopian Highlands. We questioned how the forest structure and composition varied with altitude, forest area and human influence. Location: South Gondar, Amhara National Regional State, Northern Ethiopia. Methods: The structure and species composition was assessed for 810 plots in 28 church forests. All woody plants were inventoried, identified and measured (stem diameter) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 50 publications
4
104
3
Order By: Relevance
“…Original vegetation data were obtained from five different field studies covering a total of 78 unique sites (Fig 1a): Aerts et al (2006), 10 forests, 31 20×20m plots; Aynekulu et al (2012), 1 forest, 29 50×50m plots; TewoldeBerhan (2003), 1 forest, 16 10×10m plots; Teklehaimanot et al (2004), 38 forests, plotless inventory data; Wassie et al (2010), 28 forests, 810 10×10m plots. The main criteria for including forest patches in the sampling strategy used across the studies included accessibility, permission and local knowledge of forest presence.…”
Section: Vegetation Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Original vegetation data were obtained from five different field studies covering a total of 78 unique sites (Fig 1a): Aerts et al (2006), 10 forests, 31 20×20m plots; Aynekulu et al (2012), 1 forest, 29 50×50m plots; TewoldeBerhan (2003), 1 forest, 16 10×10m plots; Teklehaimanot et al (2004), 38 forests, plotless inventory data; Wassie et al (2010), 28 forests, 810 10×10m plots. The main criteria for including forest patches in the sampling strategy used across the studies included accessibility, permission and local knowledge of forest presence.…”
Section: Vegetation Data Collection and Analysismentioning
confidence: 99%
“…In the highlands of northern and central Ethiopia, sacred groves associated with Ethiopian Orthodox Tewahedo churches and monasteries (EOTC) are known as 'church forests'. These church forests are virtually all that is left of the Ethiopian Afromontane forest (Aerts et al 2006;Wassie et al 2010;Berhane et al 2013;Jacob et al 2014) (Fig. 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of studies that suggested higher species diversity, i.e, species richness and evenness, in areas that relatively receive better conservation from human and livestock induced encroachments [13][14][15]. Moreover, compared with open areas, there are a number of studies that documented higher species diversity of wild mammals, birds, and woody species inside area exclosures and protected areas [16][17][18][19]. Unlike wild mammals and woody species richness, the species richness of birds was higher in the EHH than in the FGH.…”
Section: Species Diversities Of Wild Mammals Birds and Woody Speciesmentioning
confidence: 99%
“…These are traditionally managed small patches of remnant forest yet having a great potential for conservation of many species (Bhagwat and Rutte, 2006;Wassie et al, 2010). Similarly, the local peoples in Gobeya rural administrative of Tehuledere district have a long tradition of planting trees and conserving forests in burial sites.…”
Section: Introductionmentioning
confidence: 99%